Amica Censura: Pemikiran Nicholas Cusanus Tentang Agama-Agama, Sebuah Refleksi dan Aplikasi Terhadap Konflik Antaragama di Indonesia: Amica Censura: The Thoughts Of Nicholas Cusanus About Religions,A Reflection And Application Towards Interreligious Conflict In Indonesia - Jessica Novia Layantara (Societas Dei: Jurnal Agama dan Masyarakat, 2020)
Interreligious conflicts often occur in Indonesia, a country with various beliefs and religions. In this article, I approach these conflicts using the thoughts of Nicholas Cusanus, a medieval Catholic thinker who also faced interreligious conflict of his time, the Fall of Constantinople to Ottoman Turks. I analyze Cusanus‘ thought about religions in his works, De Pace Fidei and Cribratio Alkorani, which prove that Cusanus position on other religions is in the midst of exclusivism and pluralism. Afterwards, I will suggest reflection and application based on: 1. Interpretation of the work of Cusanus De Pace Fidei and Cribratio Alkorani, 2. Contextualizing the interpretation with interreligious conflict in Indonesia, appreciatively and critically. There are three points of reflection and application in this article: 1. A non-violent approach to other religions, 2. Sensitivity to political interests in interreligious conflict, 3. Initiates friendly and open dialogue between religions, and 4. Increase active tolerance that breaks down the dividing walls. Keywords: Nicholas Cusanus; pluralism; exclusivism; inclusivism; interreligious conflict.